1990
DOI: 10.1111/j.1528-1157.1990.tb05520.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Genetic Aspects of Idiopathic and Symptomatic Absence Seizures: Waking and Sleep EEGs in Siblings

Abstract: Epileptic activity was recorded in the waking and sleep EEG of 62.5% of 80 siblings of 38 patients with absence seizures. Epileptic discharges were noted in waking only in 8.7%, in waking as well as sleep in 28.8%, and in sleep only in 25%. Generalized, partly irregular, and slow spike-wave complexes were found, twice with lateral emphasis. Spike-wave complexes were recorded in 72% of 50 siblings of patients with idiopathic absence and in 46.7% of 30 siblings of patients with symptomatic absence. One epileptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
1
26
0
3
Order By: Relevance
“…In contrast, a different study demonstrated gender differences in the Fischer 344 rat strain, which has spontaneous absences (41). In humans, some data indicated an unequal cessation of absence seizures between sexes (42) and gender differences in the sleep-activation rate of absence seizures (43). Our data as well as those of others indicate that gender differences in absence seizures should not be underestimated in future studies.…”
Section: Gender Differencessupporting
confidence: 44%
“…In contrast, a different study demonstrated gender differences in the Fischer 344 rat strain, which has spontaneous absences (41). In humans, some data indicated an unequal cessation of absence seizures between sexes (42) and gender differences in the sleep-activation rate of absence seizures (43). Our data as well as those of others indicate that gender differences in absence seizures should not be underestimated in future studies.…”
Section: Gender Differencessupporting
confidence: 44%
“…Concordance for a spike-andwave EEG pattern among twins is reported to occur about three times more often in monozygotic than in dizygotic twins [Lennox, 1951]. Degen et al [1990] recently reported that more than 60% of siblings of children with absence seizures demonstrated epileptic EEG activity, primarily slow spike-and-wave complexes. Of particular interest is that rates of EEG epileptiform activity among siblings were similar regardless of whether the probands had idiopathic or symptomatic absence seizures.…”
Section: Absence Seizuresmentioning
confidence: 98%
“…In addition, the EEGs were obtained during napping, which was sometimes induced with psychotropic drugs. Degen and Degen [22] found few, if any, differences in sleep EEG with or without previous sleep deprivation. These authors did not feel that sleep deprivation was a sensitive method and, in addition, they considered it dangerous.…”
Section: Electroencephalographic Paroxysmal Activity During Sleep In mentioning
confidence: 99%
“…In siblings of patients with epilepsy, a number of studies [21][22][23]35] have determined the prevalence of epileptic abnormalities during sleep. The percentage of brothers and sisters of epileptic patients with spike-waves only during sleep was 20% in generalised primary tonic-clonic epilepsy, 25% in absences, 17.4% in epilepsy with rolandic paroxysms and 14.9% in febrile seizures.…”
Section: Sleep In Undetermined Epilepsy (Focal or Generalised)mentioning
confidence: 99%